2020
DOI: 10.1101/2020.10.29.20222661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of ivermectin in the prevention of COVID-19 infection among healthcare workers in India: A matched case-control study

Abstract: Background: Ivermectin is one among several potential drugs explored for its therapeutic and preventive role in COVID-19 infection. The study was aimed to explore the association between ivermectin prophylaxis and development of COVID-19 infection among healthcare workers. Methods: A hospital-based matched case-control study was conducted among healthcare workers of AIIMS Bhubaneswar, India, from September to October 2020. Profession, gender, age and date of diagnosis were matched for 186 case-control pairs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…A meta-analysis study also supports the effectiveness of ivermectin as add-on therapy in patients with Covid-19, suggesting reduction in mortality and improving clinical outcomes [ 21 ]. Recently, a hospital-based matched case-control study among healthcare workers (HCWs) in Bhubaneswar - India, reported on the efficacy of ivermectin as a prophylactic agent against COVID-19 in HCWs [ 22 ]. The study showed that two-dose ivermectin prophylaxis, each dose of 300 mcg/kg with a 72 h interval between them, was independently associated with 73 % (Adjusted Odds Ratio 0.27, 95 % Confidence Interval, 0.15−0.51) reduction in SARS-CoV-2 infection among healthcare workers in the following month.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study also supports the effectiveness of ivermectin as add-on therapy in patients with Covid-19, suggesting reduction in mortality and improving clinical outcomes [ 21 ]. Recently, a hospital-based matched case-control study among healthcare workers (HCWs) in Bhubaneswar - India, reported on the efficacy of ivermectin as a prophylactic agent against COVID-19 in HCWs [ 22 ]. The study showed that two-dose ivermectin prophylaxis, each dose of 300 mcg/kg with a 72 h interval between them, was independently associated with 73 % (Adjusted Odds Ratio 0.27, 95 % Confidence Interval, 0.15−0.51) reduction in SARS-CoV-2 infection among healthcare workers in the following month.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of 73 % in COVID-19 infection was observed in health care works for the following one month. In this study the health care workers were given two–dose of ivermectin prophylaxis at dose of 300 μg/kg with a gap of 72 hours ( Behera et al, 2020 ). This study was not peer reviewed and further clinical trials are required so that it can be used in large scale or to be used for clinical trial.…”
Section: Pharmacotherapeutic Agents Used In Treatment and Management mentioning
confidence: 99%
“…At least eight of these seem to have been completed to date, and the forthcoming publication of the relevant study results is being eagerly anticipated. [43][44][45][46][47][48][49][50][51][52][53][54][55][56]58…”
Section: Conclusion: the Way Forward For Ivermectin And Covid-19mentioning
confidence: 99%